Bahan Ajar Fisika Berbasis I-SETS (Islamic, Science, Environment, Technology, and Society) Terkomplementasi Karakter untuk Meningkatkan Motivasi Belajar Siswa - Syarifah, Bilqis Asy; Astuti, Budi (UPEJ Unnes Physics Education Journal, 2019)
Teaching materials that are commonly used do not meet the needs and criteria of the 2013 curriculum which emphasizes character education and student activity. In addition, student motivation to learn physics is also low. In this research, I-SETS physics teaching material is supplemented with characters to increase student motivation. This type of research is Research and Development (RnD). Based on validation by media and material experts as well as one practitioner it was found that physics-based I-SETS-based physics supplemented characters scored 85.03% with a very decent category. Based on the readability test results, an average score of 64.47% is included in the easy to read category. While based on the results of student motivation questionnaires, interviews and observation sheets found that I-SETS-based physics teaching materials can increase learning motivation. The results of the student character questionnaire showed that religious character, discipline, responsibility, and care for the developing environment. Meanwhile, based on observations it shows that the religious character, discipline, responsibility, and environmental care are entrenched.